Morphological Changes and Expressions of AOX1A, CYP81D8, and Putative PFP Genes in a Large Set of Commercial Maize Hybrids Under Extreme Waterlogging - Panozzo, Anna; Dal Cortivo, Cristian; Ferrari, Manuel; Vicelli, Bianca; Varotto, Serena; Vamerali, Teofilo (Frontiers in Plant Science, 2019)
Waterlogging is a severe abiotic stressor causing significant growth impairment and yield losses in many crops. Maize is highly sensitive to the excess of water, and against the background of climate change there is an urgent need for deeper insights into the mechanisms of crop adaptation to waterlogging. In the present study, changes in maize morphology at the 4-5 leaf stage and the expression of three candidate genes for flooding tolerance in plants subjected to six continuous days of waterlogging were recorded in 19 commercial hybrids and in the inbred line B73, with the aim of investigating the current variability in cultivated hybrids and identifying useful morphological and molecular markers for screening tolerant genotypes. Here it was demonstrated that root parameters (length, area, biomass) were more impaired by waterlogging than shoot parameters (shoot height and biomass). Culm height generally increased in stressed plants (by up to +24% vs. controls), while shoot biomass was significantly reduced in only two hybrids. Root biomass was reduced in all the hybrids, by an average of 30%, and significantly in 7 hybrids, while root length and area were even more severely reduced, by 30% to 55% vs. controls, depending on the hybrid. The earlier appearance of aerial roots seemed to be associated with greater root injuries. In leaves, the transcript of the PFP enzyme (phosphofructokinase), which is involved in glycolytic reactions, was markedly up-regulated (up to double the values) in half the waterlogged hybrids, but down-regulated in the others. The transcript of CYP81D8 (ROS-related proteins) in waterlogged plants exhibited relevant increases or strong decreases in level, depending on the hybrid. The transcript of the AOX1A gene, coding for a mitochondrial respiratory electron transport chain-related protein, was markedly down-regulated in all the treated hybrids. Expression analysis of these genes under extreme waterlogging only partially correlate with the shoot and root growth impairments observed, and AOX1A seems to be the most informative of them.